Ultrastructural features of normal sprague dawley's brain cells under transmission electron microscope (TEM) / Wan Mohd Akmal Wan Sabri - Wan Sabri, Wan Mohd Akmal (2014)
Limited references involving the normal ultrastructure of brain cells image especially neurons by using Transmission Electron Microscope (TEM) at UiTM Faculty of Pharmacy's Imaging Center (iMACE) had made many researches related to neurons difficult to be observed and compared with the normal structure. As for that, this study will serve as standard reference for future brain related studies of TEM image in iMACE. Transmission Electron Microscope (TEM) which is the latest technology of electron microscope using the charge coupled device (CCD) camera had been used to observed the ultrastructure of neurons. The structure that are successful to be observed are common structures which including nucleus, mitochondria, Golgi apparatus, agranular reticulum, cytoplasm, vacuoles and cell membrane. On the other hand, specialized organelled in neuron tha had been observed are neurofilaments and Nissl bodies. However, synapses were unable to be identified in the micrograph.